Accuracy of Mechanical Torque Devices for Implants Used in Brazilian Dental Offices - Santos, Gildo Coelho; Passos, Sheila Pestana; Moraes Coelho Santos, Maria Jacinta (Quintessence Publishing Co Inc, 2011)
The purpose of this study was to determine the accuracy of mechanical torque devices in delivering target torque values in dental offices in Salvador, Brazil. A team of researchers visited 16 dental offices, and the clinicians applied torque values (20 and 32 Ncm) to electronic torque controllers. Five repetitions were completed at each torque value and data were collected. When 20 Ncm of torque was used, 62.5% of measured values were accurate (within 10% of the target value). For 32 Ncm, however, only 37.5% of these values were achieved. Several of the tested mechanical torque devices were inaccurate. Int J Prosthodont 2011;24:38-39.